Salmonella Infection Drives Promiscuous B Cell Activation Followed by Extrafollicular Affinity Maturation - Di Niro, Roberto; Lee, Seung-Joo; Vander Heiden, Jason A.; Elsner, Rebecca A.; Trivedi, Nikita; Bannock, Jason M.; Gupta, Namita T.; Kleinstein, Steven H.; Vigneault, Francois; Gilbert, Tamara J.; Meffre, Eric; McSorley, Stephen J.; et al. (Immunity (Cambridge, Mass.), 2015)
The B cell response to Salmonella typhimurium (STm) occurs massively at extrafollicular sites, without notable germinal centers (GCs). Little is known in terms of its specificity. To expand the knowledge of antigen targets, we screened plasmablast (PB)-derived monoclonal antibodies (mAbs) for Salmonella specificity, using ELISA, flow cytometry, and antigen microarray. Only a small fraction (0.5%–2%) of the response appeared to be Salmonella-specific. Yet, infection of mice with limited B cell receptor (BCR) repertoires impaired the response, suggesting that BCR specificity was important. We showed, using laser microdissection, that somatic hypermutation (SHM) occurred efficiently at extrafollicular sites leading to affinity maturation that in turn led to detectable STm Ag-binding. These results suggest a revised vision of how clonal selection and affinity maturation operate in response to Salmonella. Clonal selection initially is promiscuous, activating cells with virtually undetectable affinity, yet SHM and selection occur during the extrafollicular response yielding higher affinity, detectable antibodies. •Salmonella (STm) induces a large plasmablast response that is seemingly non-specific•The response is actually specific with affinities that are too low to detect•Extrafollicular SHM leads to affinity maturation and detectable affinities•The STm response differs markedly from the classical GC response to model antigens B cell responses to Salmonella proceed via extrafollicular rather than germinal center pathways. Shlomchik and colleagues show that such responses are characterized by promiscuous, yet specific B cell activation, followed by extrafollicular somatic hypermutation, affinity maturation, and isotype switch.